2020
DOI: 10.1038/s41598-020-58508-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intraocular gas using magnetic resonance imaging after pars plana vitrectomy with gas tamponade for rhegmatogenous retinal detachment

Abstract: We used magnetic resonance imaging (MRI) to assess how a patient's posture affects intraocular gas changes and whether the postoperative prone position is required after pars plana vitrectomy (ppV) with gas tamponade for rhegmatogenous retinal detachments (RRDs). eight patients with RRDs who underwent ppV combined with cataract surgery with gas tamponade were prospectively included. they underwent MRi examination both in the prone and supine positions. We separated the retina into four parts: superior-posterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
0
13
1
Order By: Relevance
“…Next, we separated the 3-D vitreous cavity at 1:30, 4:30, 7:30, and 10:30 into four quadrants and then defined the position of the ora serrata of the inferior retina as the anatomical differences as 6.7 mm posterior to the limbus. Then, we defined the equator as 6.5 mm posterior to the ora serrata in the inferior retinal area, according to the vortex vein ampullae 15 , 16 . Therefore, the inferior quadrant of the retina was separated into two parts, inferior-anterior and inferior-posterior (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we separated the 3-D vitreous cavity at 1:30, 4:30, 7:30, and 10:30 into four quadrants and then defined the position of the ora serrata of the inferior retina as the anatomical differences as 6.7 mm posterior to the limbus. Then, we defined the equator as 6.5 mm posterior to the ora serrata in the inferior retinal area, according to the vortex vein ampullae 15 , 16 . Therefore, the inferior quadrant of the retina was separated into two parts, inferior-anterior and inferior-posterior (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, all gas cover rates in each quadrant in prone position were < 100% when the gas volume was 80%. Furthermore, we have previously reported that if patients were superficially maintained in a strict prone position, the supraduction angle (°) of the eyeball to the perpendicular line was positive (16.1°; range, 6.3-29.9) 16 . In the current study, in the prone with closed eyes position, the gas cover rates of the nasal and temporal retinas were < 100%, despite the intraocular gas volume being 90%.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 A–F shows resting positions of the 24 mm eye model, which represents the postoperative body positions. We have previously reported that even if patients superficially maintain a strict prone position with eyes closed, the mean supraduction angle (°) of the eyeball to the perpendicular line is positive (16.1°) 16 . Therefore, six resting positions of the eyeball examined were as follows: Supine: The direction of the eyeball is 90° upward from the horizontal line Sitting: The direction of the eyeball is parallel to the horizontal line Prone with closed eyes: The supraduction angle of the eyeball to the perpendicular line is 16.1° Prone: The direction of the eyeball is 90° downward from the horizontal line Lower temporal: The eyeball was rotated 90° from the sitting position, such that the temporal retina was on the horizon side Lower nasal: The eyeball was rotated 90° from the sitting position, such that the nasal retina was on the horizon side …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations